Social-Cultural Preconditions of the Formation of Cynicism - Babajanyan, Levon (Bulletin of Yerevan University E: Philosophy, Psychology, 2013)
Throughout history cynicism has always accompanied human thought as a refusing-denialist attitude towards sociality. In industrial society due to political, economic, historical, social and cultural transformations a new social-cultural space was formed where formerly functioning meaning directives of being are distorted. During the formation of new social-cultural environment new opportunities for cynicism emerge. In the context of modernity cynicism can be described by a number of functional and phenomenological peculiarities. Social-political, social-economic, socialanthropological and moral-psychological functional factors of cynicism are distinguished. When these factors are analyzed it turns out that cynicism, a phenomenon that can surface both on individual and social levels, is such an attitude that contains dangerous obstacles for giving a meaning to being. Overcoming cynicism may become an issue of vital significance for ensuring survival of both each individual and the whole society.